2020
DOI: 10.1093/icesjms/fsaa013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sampling strategies for age determination of cod (Gadus morhua) sampled at the North Sea International Bottom Trawl Survey

Abstract: The North Sea cod stock assessment is based on indices of abundance-at-age from fishery-independent bottom trawl surveys. The age structure of the catch is estimated by sampling fish for otoliths collection in a length-stratified manner from trawl hauls. Since age determination of fish is costly and time consuming, only a fraction of fish is sampled for age from a larger sample of the length distribution and an age–length key (ALK) is then used to obtain the age distribution. In this study, we evaluate ALK est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…However, in order to generate inputs used in formal assessments, analysts should likely include sampling of length frequency information at the tow level in the bootstrapping process as well (i.e., add a level of sampling in the estimator for the length expansion process). Other options for addressing this issue would be to: (1) explore spatially-aggregated (or constant) age-length keys that share information with a stratum that is missing a length bin necessary for expansion of ages, or (2) share age-length key information from nearby tows in other strata when this mismatch occurs as Jourdain et al (2020) did.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in order to generate inputs used in formal assessments, analysts should likely include sampling of length frequency information at the tow level in the bootstrapping process as well (i.e., add a level of sampling in the estimator for the length expansion process). Other options for addressing this issue would be to: (1) explore spatially-aggregated (or constant) age-length keys that share information with a stratum that is missing a length bin necessary for expansion of ages, or (2) share age-length key information from nearby tows in other strata when this mismatch occurs as Jourdain et al (2020) did.…”
Section: Discussionmentioning
confidence: 99%
“…A major question that is often asked in survey science is how to optimize the distribution of biological sampling efforts across species without increasing survey effort (number of ships, number of tows conducted, number of working days, etc.). For example, previous research on sampling protocols for Atlantic cod (Gadus morhua) on the North Sea International Bottom Trawl Survey (IBTS) conducted by the International Council for the Exploration of the Sea (ICES) has shown that the number of fish sampled for ageing could be reduced by at least 50% without a substantial loss of precision in the estimation of abundance-at-age (Jourdain et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The monitoring and surveillance of fish diversity and the estimation of fish abundance are usually carried out with methods based on visual census, remotely operated vehicles (ROVs), as well as fishing techniques, such as bottom trawls (Thompson et al, 1982;Groeneveld, 2000;Sward et al, 2019;Trenkel et al, 2019). Despite all the standardization and optimization protocols, these traditional sampling methods provide information only on short sampling/ monitoring time within the stations that span over a few minutes to an hour (Baudrier et al, 2018;Sward et al, 2019;Jourdain et al, 2020) and can be altered by behavioral responses, like observer or gear avoidance. In addition, fishing methods are invasive and cause disturbances and disequilibrium in the marine ecosystems, and can therefore threaten the conservation efforts for marine species.…”
Section: Introductionmentioning
confidence: 99%